2002
DOI: 10.1016/s0735-1097(01)01697-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with fetal, neonatal or childhood diagnosis of isolated congenital atrioventricular block

Abstract: Pre-natal diagnosis of CAVB is associated with high fetal and neonatal mortality. Among survivors, whether the diagnosis is made before or after birth, most undergo pacemaker implantation by adulthood, with earlier intervention and a significantly greater need for reintervention among those diagnosed in utero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(112 citation statements)
references
References 25 publications
6
101
0
5
Order By: Relevance
“…Fetal Bradyarrhythmia With CHD was not a risk factor. 20, 21 Our previous study of fetal complete AVB without CHD also showed that the fetal ventricular heart rate was not associated with prognosis. 7 In contrast, our current study revealed that the ventricular heart rate was related to the outcome in fetuses with bradyarrhythmia with CHD.…”
Section: Pmi In the Neonatal Periodmentioning
confidence: 94%
See 1 more Smart Citation
“…Fetal Bradyarrhythmia With CHD was not a risk factor. 20, 21 Our previous study of fetal complete AVB without CHD also showed that the fetal ventricular heart rate was not associated with prognosis. 7 In contrast, our current study revealed that the ventricular heart rate was related to the outcome in fetuses with bradyarrhythmia with CHD.…”
Section: Pmi In the Neonatal Periodmentioning
confidence: 94%
“…22-25 High intrauterine mortality in cases of left atrial isomerism with complete AVB is often preceded by development of heart failure. 20, 21 A high incidence of poor cardiac function and hydrops may partially explain the poor prognosis. We suggest that myocardial dysfunction could be ascribed to bradycardia and intrinsic ventricular dysfunction proceeding from the CHD.…”
Section: Pmi In the Neonatal Periodmentioning
confidence: 99%
“…Related to treatment of bradyarrhythmias, early treatment of fetuses affected by atrioventricular delayed conduction or complete heart block with maternally administered dexamethasone or ritodrine may improve or prevent the loss of atrioventricular nodal conduction [88,89]. The treatment of fetal tachycardia remains controversial.…”
Section: Fetal Arrhythmiasmentioning
confidence: 99%
“…31 Cases were diagnosed from fetal life through childhood. There were a total of 102 cases, divided into three groups.…”
Section: Classification and Progression Of Heart Blockmentioning
confidence: 99%